Marine rocky reef assemblages and lithological properties of substrates are connected at different ecological levels. Issue 1 (31st December 2022) - Canessa, M.; Bavestrello, G.; Guidetti, P.; Navone, A.; Trainito, E.
Abstract: Recent studies suggest that the lithological properties of hard substrates play an important role in influencing the diversity and structure of marine assemblages involving macroalgae, sessile organisms and vagile animals like heterobranchs gastropods and fishes. The present study aims at exploring whether the influence of different substrates (limestone vs granite) could drive the occurrence of different vagile groups (crustacean decapods, echinoderms and fishes). The study was carried out at the "Tavolara-Punta Coda Cavallo" Marine Protected Area (NE Sardinia, Mediterranean Sea) where substrates of different lithology, namely granites and limestones, occur on a local spatial scale. The diversity and the abundance of 16 vagile species (four crustaceans, seven echinoderms and five fishes) were investigated by the analysis of photographs (2352 images) collected in 20 sites (10 limestones and 10 granites), between 30 and 50 m depth. Statistical analyses showed a clear-cut separation between the assemblages assessed on the two lithological substrate types, with assemblages on granites that were tightly grouped and those on limestones more dispersed. The total species richness did not significantly vary between limestones and granites. Galathea strigosa and Marthasterias glacialis were exclusively recorded on granites, while Palinurus elephas, Scyllarides latus, Arbacia lixula, Ophidiaster ophidianus and Serranus scriba were exclusively found on limestones. The observed patterns could be partially explained by multiple factors related to lithology: i) the different availability of preferred food sources, potentially influenced by substrate type; ii) the site geomorphology, that could provide different dens and refuges (in terms of quantity and types of shelters) suitable for different species; iii) the colour of different substrates enhancing the mimicry of different species according to their livery and camouflage ability. Our and literature data suggest that the substrate type in rocky reefs could interact with other environmental factors (i.e., light intensity related to depth) in shaping the structure of rocky-reef assemblages.